2010
DOI: 10.17973/mmsj.2010_11_201016
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Composite Zn-Ptfe Coatings

Abstract: Commonly applied theories of self-excited vibrations in machine tools are prevailingly based on frequency domain analysis of linear models, and in most cases only focus on evaluation of stability limits of strictly linear systems. In this way the behaviour of more stable or more unstable systems cannot be studied and analyzed. Neither is it possible to study certain important nonlinear effects because of limitations connected with the classical representation of systems only in the frequency domain. Evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Some particles such as: silver [8], B4C [9], CeO2 [10], graphite [11], TiO2 [12], V2O5 [13], SiC [14] were used as dispersed phases for obtaining composite coatings in zinc matrix, but studies with polymeric particles used as dispersed phase are relatively limited. It was reported only few studies with composite materials obtained in zinc matrix with dispersed phase polymers such as polymethylmethacrylate (PMMA) [15], polystyrene (PS) [16], PEDOT (poly (3,4-ethylenedioxythiophene) [17], polytetrafluoroethylene (PTFE) [18], polyaniline (PANI) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Some particles such as: silver [8], B4C [9], CeO2 [10], graphite [11], TiO2 [12], V2O5 [13], SiC [14] were used as dispersed phases for obtaining composite coatings in zinc matrix, but studies with polymeric particles used as dispersed phase are relatively limited. It was reported only few studies with composite materials obtained in zinc matrix with dispersed phase polymers such as polymethylmethacrylate (PMMA) [15], polystyrene (PS) [16], PEDOT (poly (3,4-ethylenedioxythiophene) [17], polytetrafluoroethylene (PTFE) [18], polyaniline (PANI) [19].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons is necessary to improve the corrosion behaviour of pure zinc coatings using different disperse phase included in the zinc matrix. Phenol formaldehyde resin and epoxy resin are used usually as polymeric coatings because act as a barrier to protect steel from different corrosion environments and are widely used for industrial applications [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is necessary to improve these coatings by adding different organic and inorganic particles. For example, it was reported that new composite coatings were obtained by co-deposition using metal matrix and different particles such as SiO 2 , TiO 2 , ZrO 2 nanoparticles, carbon nanotubes, polytetrafluorethylene (PTFE), polyaniline (PAN), polymethylmethacrylate (PMMA) exhibited improved corrosion properties when compared with conventional zinc [ 5 , 6 , 7 , 8 , 9 , 10 ]. In these composite coatings, mixed layers of corrosion products from the metal and particles in the composite coating often appear and demonstrate a synergistic interaction which contributes to the improvements in properties of hybrid layers.…”
Section: Introductionmentioning
confidence: 99%